Operational Evaluation of a Throughabout to Give Priority to Public Transport at Standard Roundabouts - Sajjad Zakeri; Abdoul-Ahad Choupani (Journal of Advanced Transportation)
The presence of roundabouts in the central business districts (CBD) of cities can reduce the travel speed of bus rapid transit (BRT) along the radial routes. A throughabout is an unconventional and low-cost design in which the central island is split to provide exclusive lanes for major traffic streams. Although the operation of throughabout has been limitedly investigated for private transport, it has been less considered by designers for public transport and for increasing the speed of the BRT system. The current study aims to evaluate the effects of throughabouts on private and public transports and to compare the design with standard roundabouts and conventional intersections. The calibrated and validated results of the microsimulation tool (AIMSUN) indicated that the throughabout improved the travel time of both public and private transports through better use of the space and kept the traffic flowing at all volume levels. The travel speed of the BRT in the throughabout was remarkably stable in both signal-controlled and unsignalized intersections. The standard roundabout was the second-best design. The throughabout can be very helpful in corridors along which the demand for the bus transit is high and the system needs to receive priority.